PERAN MEDIA SOSIAL DALAM STRATEGI PUBLIC RELATIONS UNTUK MEMBANGUN BRAND IMAGE DI LEMBAGA PENDIDIKAN - Parati; Eka Diana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Social media has become an important tool in shaping the image of schools. However, not all educational institutions are able to manage it effectively. This study aims to analyze the role of social media in public relations strategies to shape the image of schools. The approach used is qualitative with a case study type that occurred at SMAN 1 Paiton Probolinggo. Data was collected through interviews with school officials, observations of social media activities, and content analysis of the school's official accounts. The results indicate that strategic use of social media can enhance a school's visibility and reputation. Informative, educational, and interactive content has proven effective in building audience engagement and strengthening relationships with students, parents, and the community. The impact of this research not only provides practical contributions to social media management in school environments but also serves as a reference for other schools in developing digital communication strategies and encourages educational institutions to be more adaptive to technological advancements, making social media a primary tool in shaping public image and trust.